2019
DOI: 10.1371/journal.pone.0216881
|View full text |Cite
|
Sign up to set email alerts
|

Changes in phosphorus fractions associated with soil chemical properties under long-term organic and inorganic fertilization in paddy soils of southern China

Abstract: The identification of phosphorus (P) fractions is essential for understanding the transformation and availability of P in paddy soils. To investigate the soil P fractions associated with soil properties under long-term fertilization, we selected three fertilization treatments, including no fertilization (CK), chemical fertilizers (NPK) and chemical fertilizers combined with manure (NPKM), from three long-term experiments located in Nanchang (NC), Jinxian (JX) and Ningxiang (NX). The results showed that chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 48 publications
6
47
0
Order By: Relevance
“…Histosols d and Histosls w : means of the three drained and three rewetted peatlands of the present study, respectively. Sources: [46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Phosphorus Fractionsmentioning
confidence: 99%
“…Histosols d and Histosls w : means of the three drained and three rewetted peatlands of the present study, respectively. Sources: [46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Phosphorus Fractionsmentioning
confidence: 99%
“…There could be many factors regulating P in paddy soil under long-term fertilization. In a previous study, Ahmed et al [21] found that the combined application of manure and inorganic fertilizers increased the labile-P fraction, and different soil properties (pH, SOM, total P and Olsen-P) showed different relationships with P fractions, however, the authors did not explain the mechanism of P pools transformation, mobility and uptake in paddy soils associated with soil nutrient stoichiometry. One of the most important factors for P mobility in paddy soil could be soil nutrient stoichiometry, coupling and interactions of the C, N and P cycles [2224].…”
Section: Introductionmentioning
confidence: 97%
“…In a previous study, we observed that application of wheat straw or pig manure in combination with inorganic fertilizer increased the phosphatase activities and PUE 24 . Addition of manure can increase the soil pH due to alkalinity of manure 25 . However, liming is considered one of the most effective strategies to mitigate soil acidification, which can increase P availability in acidic soil 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%